Association between habitual physical activity on episodic memory strategy use and memory controllability - Paul D. Loprinzi (Tabriz University of Medical Sciences, 2019)
Background: The primary objective of this study was to evaluate the association between habitual physical activity engagement and perceived controllability of memory function. Secondary objectives included the evaluation of physical activity on memory strategy use, and whether the latter mediates the relationship between physical activity on memory controllability. Methods: Two-hundred and nine young adults (Mage=25 y) completed a brief survey evaluating physical activity (Physical Activity Vital Signs Questionnaire), memory strategy use (Memory Functioning Questionnaire), and memory controllability (Memory Controllability Inventory). Results: Physical activity was not associated with memory strategy use (β=0.68; 95% CI: -1.25,2.62; P=0.48), nor was memory strategy use associated with memory controllability. Physical activity was consistently associated with various attributes of memory controllability, including Present Ability (β=1.10; 95% CI: 0.07, 2.12; P=0.03), Potential Improvement (β=0.84; 95% CI:0.05, 1.63; P=0.03), Effort Utility (β=0.87; 95% CI: 0.11, 1.61; P=0.02), Inevitable Decrement (β=-1.19; 95% CI: -2.19, -0.19; P=0.02) and Alzheimer's likelihood (β=-1.21; 95% CI: -2.29,-0.12; P=0.02). Conclusion: Physical activity is consistently associated with greater perceptions of memory controllability. Future longitudinal and experimental work on this topic is warranted to evaluate if physical activity can foster an individual's ability to modify their behavior and cognitions to enhance and preserve memory function.